Parametric Study of Stiffeners in Steel Composite Tub Girders - Pushpangadan, Silpa; S. Menon, Arjun; Sofi, A (International Journal of Engineering and Technology, 2018)
Closed structural sections (rectangular, circular, trapezoidal shape) possess high rotational rigidity compared to open sections like I girder. For highly curved bridges, closed sections with high torsional rigidity is an absolute choice. This paper suggests the use of steel â€“ composite Tub girder instead of concrete I girder in rail bridges. Stiffeners were used to strengthen the girder. Deflection and stress study has been done for the entire girder on various thickness of stiffeners under different loading.Â Â